The Importance of Maturity in Marriage From an Islamic Legal Perspective - Novitasari, Ane Fany; Luth, Thohir; Djumikasih, Djumikasih; Chanifah, Nur (Journal of Legal Studies, 2024)
This study seeks to examine the notion of marital maturity through the lens of Islamic jurisprudence. It employs a normative legal research methodology, combining philosophical insights, statutory regulations, and contextual analysis. The analytical techniques involve surveying, conducting question-and-answer sessions, thoroughly reading legal materials, and employing deductive analysis. The research results show that in Islamic law, maturity in marriage refers to the boundaries of individuals who have reached puberty. The importance of building a household based on maturity is to create psychological maturity in both partners, both husband and wife. Islamic law underscores the importance of individuals being mentally, physically, and psychologically prepared for marriage, emphasizing that it is a form of worship. Therefore, building a mature and responsible household is expected in Islamic teachings.